2020
DOI: 10.15282/jmes.14.2.2020.11.0523
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic field enhancement technique in the fluid flow gap of a single coil twin tube Magnetorheological damper using magnetic shields

Abstract: Smart dampers in the automobile suspension system bring a precise balance between the ride comfort and stability through a controllable damping coefficient. Energy absorbed by a Magnetorheological (MR) damper is a dependent function of flux density in the fluid flow gap. In this paper, magnetic field enhancement technique in the form of a single cylindrical shield and sandwich cylindrical shield is incorporated in a twin tube single coil MR damper. The field strength in different configurations of MR damper ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Therefore, adjusting the current in the piston coil can be a good way to adjust the damping force. As shown in Figure 1, the coil winding modes of the dampers are divided into single-coil [15] and double-coil [6] modes. The structure of the single-coil shear valve magnetorheological damper is shown in Figure 2.…”
Section: Parametric Modeling Of Single-coil Mr Dampermentioning
confidence: 99%
“…Therefore, adjusting the current in the piston coil can be a good way to adjust the damping force. As shown in Figure 1, the coil winding modes of the dampers are divided into single-coil [15] and double-coil [6] modes. The structure of the single-coil shear valve magnetorheological damper is shown in Figure 2.…”
Section: Parametric Modeling Of Single-coil Mr Dampermentioning
confidence: 99%
“…In combination with Equations ( 13) and ( 16) to (19), the electromagnetic field distribution inside the MR damper can be described as:…”
Section: Electromagnetic Field Modelmentioning
confidence: 99%
“…Only the state of its internal stable magnetic field was analyzed. The current density was applied to the excitation coil area according to Equation (19). The distribution of the electromagnetic field inside the proposed damper when the given current was 1 A is shown in Figure 7.…”
Section: Simulation Analysis Of Electromagnetic Fieldmentioning
confidence: 99%
See 1 more Smart Citation
“…When constructing twin-tube MR dampers that are outfitted with a single coil, it is common to practice using magnetic shields and sandwiched magnetic shields. This research was conducted by Ganesha et al [15] and concluded that the experiment was successful, as evidenced by improvements in suspension control, ride comfort, and deflection of tires.…”
Section: Introductionmentioning
confidence: 99%